Occupational exposure to solvents and lung function decline: A population based study. Issue 7 (26th April 2019) - Alif, Sheikh M; Dharmage, Shyamali; Benke, Geza; Dennekamp, Martine; Burgess, John; Perret, Jennifer L; Lodge, Caroline; Morrison, Stephen; Johns, David Peter; Giles, Graham; Gurrin, Lyle; Thomas, Paul S; et al.
Abstract : Rationale: While cross-sectional studies have shown associations between certain occupational exposures and lower levels of lung function, there was little evidence from population-based studies with repeated lung function measurements. Objectives: We aimed to investigate the associations between occupational exposures and longitudinal lung function decline in the population-based Tasmanian Longitudinal Health Study. Methods: Lung function decline between ages 45 years and 50 years was assessed using data from 767 participants. Using lifetime work history calendars completed at age 45 years, exposures were assigned according to the ALOHA plus Job Exposure Matrix. Occupational exposures were defined as ever exposed and cumulative exposure -unit- years. We investigated effect modification by sex, smoking and asthma status. Results: Compared with those without exposure, ever exposures to aromatic solvents and metals were associated with a greater decline in FEV1 (aromatic solvents 15.5 mL/year (95% CI −24.8 to 6.3); metals 11.3 mL/year (95% CI −21.9 to – 0.7)) and FVC (aromatic solvents 14.1 mL/year 95% CI −28.8 to – 0.7; metals 17.5 mL/year (95% CI –34.3 to – 0.8)). Cumulative exposure (unit years) to aromatic solvents was also associated with greater decline in FEV1 and FVC. Women had lower cumulative exposure years to aromatic solvents than men (mean (SD) 9.6 (15.5) vs 16.6 (14.6)), but greater lung function decline than men. We also found association between ever exposures to gases/fumes or mineral dust and greater decline in lung function. Conclusions: Exposures to aromatic solvents and metals were associated with greater lung function decline. The effect of aromatic solvents was strongest in women. Preventive strategies should be implemented to reduce these exposures in the workplace.